Production and Export of Green Beans (Phaseolus vulgaris L.) - Hernández Ocampo, Gustavo Adolfo; Morales Rivera, Rommel Noé; Valdivia Lorente, Rodolfo Ramón; Castillo, Edwin; Palma, Santos (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the environment (PROGRESA). This report aims to share the stakes, risks, lessons learned, and outcome of PROGRESA’s initiative to promote and assist Nicaraguan vegetable producers in the production and export of green beans.